Study of shear performance of steel-timber composite connection with different shear connectors - Ernian Zhao; Qi Song; Jing-Ru Yao; Xin Zhang (Case Studies in Construction Materials, 2024)
The shear resistance of steel-timber composite (STC) connections largely depends on the shear performance of shear connectors. Three types of shear connectors, i.e., welded stud, screw, and screw-grout were considered in this paper. The failure modes, load-slip curves, shear stiffnesses, and shear carrying capacity of the STC connection with three different connectors were experimentally and theoretically investigated under various shear connector diameters and glulam panel thicknesses. The experimental results indicated that the shear carrying capacity and stiffness of the welded stud connections are 1.49 and 5.17 times higher than those of the screw connection under identical cases, respectively. The failure patterns of welded stud connection were characterized by shear failure of the stud, crushing failure in the grout blocks and splitting failure of the glulam panel. In contrast to welded stud connections, screw and screw-grout connections exhibited significant crushing failure of glulam. It indicated that the grout used in welded stud connection can effectively mitigate or avoid crushing failure in the glulam panel. A simplified and feasible theoretical formula was developed to predict the shear carrying capacity of the STC connection with welded stud connector. Compared with the predictions of GB 50017-2017, AISC 360-16, and EC 4, the developed formula for the shear carrying capacity of welded stud connection provided a reasonable prediction with an error within 15 %.